Організаціно-технологічні засади процесу надання готельних послуг - Колєсніченко, Анастасія Сергіївна (НТУ "ХПІ", 2017)
Розкрито специфіку технології роботи готелів, визначено її складові через побудову гостьового циклу в контексті розвитку індустрії гостинності, систематизовано організаційні засади процесу надання готельних послуг, відповідно до етапів гостьового циклу, з урахуванням основних принципів формування технологічних ланцюгів, що сприятиме удосконаленню організаційно-технологічної структури та вирішенню актуальних завдань підвищення ефективності функціонування цієї сфери обслуговування.

The processes of globalization and integration that are characterisise the global hotel industry have been discussed as reflected points in the creation of large corporations and hotel chains. It is claimed that these tends are becoming one of the most widely used hotel management tools used in world practice. In turn, this requires the use of the latest organizational and technological techniques to ensure the dynamic development of each particular hotel and the entire industry as a whole.The is determined the essence of the components of the technology of hotels functioning through the construction of the guest cycle in the context of the development of the hospitality industry. The are systemized the organizational principles of the structure of the process of providing hotel services in accordance with the stages of the guest cycle, taking into account the main principles of the technological chains. That circumstances will facilitate the improvement of the organizational and technological basis and for the formulation of actual tasks improving the efficiency of this service sector.
The organizational and technological fundamentals of the providing hotel services process
Keywords: гостьовий цикл; технологічні ланцюги; організація; готельний сервіс; guest cycle; technological circuits; organization